ANALISIS PENGARUH PRIVASI DAN KEAMANAN TERHADAP NIAT BERTRANSAKSI SECARA ONLINE DI SHOPEE.CO.ID (STUDI KASUS MAHASISWA STIE SUMBAR PARIAMAN) - Rini Afrianti; Sintia Vella Nazli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The purpose of this study was to find out how the influence of privacy and security on the intention to transact online at shopee.co.id The population in this study were shopee.co.id application users at STIE Sumbar Pariaman. The sampling technique used a purposive sampling method with the criteria of shopee.co.i users at STIE Sumbar Pariaman who had purchased online at shopee.co.id. Samples were 100 respondents with data collection techniques using questionnaires. Data analysis techniques in this study used descriptive analysis techniques and multiple linear regression. The results of this study indicate that: (1) Privacy does not significantly influence the intention to transact online at shopee.co.id, as evidenced by the value of tcount of 1.319 with a significance value of 0.190, greater than 0.05 (2) security has a significant effect on the intention to transact online at shopee.co.id, evidenced from the value of tcount of 5.893 with a significance value of 0.000, smaller than 0.05 (3) Privacy and security simultaneously have a significant effect on the intention to transact online at shopee.coid, as evidenced by the results of Fcount of 34,834 with a significance of 0,000.